2022
DOI: 10.1021/jasms.2c00046
|View full text |Cite
|
Sign up to set email alerts
|

IR Spectroscopic Characterization of Methane Adsorption on Copper Clusters Cun+ (n = 2–4)

Abstract: The interaction of CH4 with cationic copper clusters has been studied with infrared-multiple photon dissociation (IRMPD) spectroscopy. Cu n + (n = 2–4) formed by laser ablation were reacted with CH4. The formed complexes were irradiated with the IR light of the free-electron laser for intracavity experiments (FELICE), and the fragments were mass-analyzed with a reflectron time-of-flight mass spectrometer. The structures of the Cu n +–CH4 complexes are assigned on the basis of comparison between the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
(65 reference statements)
0
10
1
Order By: Relevance
“…3 conguration at h 2 mode found here is reasonable in comparison to the adsorption of CH 4 on differently active centers, i.e., transition metal [M(pyridine) n ] 2+ complexes, 37 single-atom Fedoped graphene and h-BN sheets, 38 and Cu n+ copper clusters. 39 However, in our case, the binding energy of methane on Cu 2+ of ZIF-204 is at-most half of the methane binding energies on the structures mentioned above. The smaller interaction energy can be attributed to either the electronic properties of metal centers or the effect of coordinated ligands.…”
Section: Adsorption Of Ch 4 Over Zif-204contrasting
confidence: 46%
“…3 conguration at h 2 mode found here is reasonable in comparison to the adsorption of CH 4 on differently active centers, i.e., transition metal [M(pyridine) n ] 2+ complexes, 37 single-atom Fedoped graphene and h-BN sheets, 38 and Cu n+ copper clusters. 39 However, in our case, the binding energy of methane on Cu 2+ of ZIF-204 is at-most half of the methane binding energies on the structures mentioned above. The smaller interaction energy can be attributed to either the electronic properties of metal centers or the effect of coordinated ligands.…”
Section: Adsorption Of Ch 4 Over Zif-204contrasting
confidence: 46%
“…To summarize the results on TM cluster-CH 4 complexes and without attempting to go in-depth here, recent data from IR spectroscopic investigations can be categorized into either identifying weakly bound, intact CH 4 ligands with barely to markedly activated C–H bonds as seen for Fe n + ( n = 2–4), 336 Pt n + ( n = 3–5), 63 a and Cu n + ( n = 2–4), 337 or partly dehydrogenated species like in the case of Au n + ( n = 2–4) 64 c and Ta 4 + . 335 The later example shows for ions of composition Ta 4 [CH 2 ][CH 4 ] m + ( m = 0, 1, 2…, including other methane isotopologues) the presence of a carbide–dihydride core, H 2 Ta 4 C + , with CH 4 ligands essentially acting as messenger, while complexes with composition Ta 4 [CH 4 ] m + contain only intact CH 4 .…”
Section: Probing Ligand Binding and Chemistry On Metal Clustersmentioning
confidence: 99%
“…To summarize the results on TM cluster-CH 4 complexes and without attempting to go in-depth here, recent data from IR spectroscopic investigations can be categorized into either identifying weakly bound, intact CH 4 ligands with barely to markedly activated C-H bonds as seen for Fe n + (n = 2-4), 336 Pt n + (n = 3-5), 63a and Cu n + (n = 2-4), 337 or partly dehydrogenated species like in the case of Au n + (n = 2-4) 64c and Ta 4 + . 335 335 For cationic gold cluster-methane complexes, features are seen outside the typical range of the C-H deformation modes of 1200-1600 cm À1 .…”
mentioning
confidence: 99%
“…Gas-phase reactions, permitting clarification of intrinsic chemical behavior of reactive species with atomistic precision facilitated by state-of-the-art mass spectrometry combined with ingeniously designed reactors, offer a unique approach to characterize the reactivity of atomically precise metal species that compositionally resemble the active sites of real-life catalysts. Early in the 1990s, research efforts had been made to prepare single-metal cations anchored by organic ligands of benzyne, such as MC 6 H 4 + (M = Fe, Sc, and Cr), but reactivity investigation with alkanes demonstrated that these MC 6 H 4 + complexes were unreactive toward methane, similar to the inert behavior of corresponding bare M + ions. Significant enhancements of the ability of atomic M + (M = Fe and Ni) to adsorb and activate CH 4 were later achieved when modulated by other ligands of benzene (C 6 H 6 ), corannulene (C 20 H 10 ), coronene (C 24 H 12 ), C 60 , or the phenyl group (C 6 H 5 ) .…”
mentioning
confidence: 99%
“…Distinctly, the acetonitrile (CH 3 CN) ligand was found to switch the mechanism of methane activation mediated by diatomic cation ZnO + , ultimately resulting in the improvement of product selectivity at the expense of activity. In sharp contrast with the extensively investigated single-metal systems, the preparation and reactivity study of the ligated or “supported” metal clusters, which represent important classes of heterogeneous ,, catalysts for many reactions, were rarely investigated in the gas phase, despite that a considerable number of free metal clusters and metal compound (oxide, carbide, nitride, and boride) clusters being capable of activation and functionalization of methane under mild conditions have been reported in the literature. ,, , …”
mentioning
confidence: 99%